Does removal of mammalian predators significantly affect success of simulated nests in linear habitats? Case study on American mink Mustela vison \& Predation on simulated duck nests in relation to nest density and habitat type - Padyšáková, Eliška (Jihočeská univerzita, 2007)
Práce se zabývá studiem predace hnízd vodních ptáků. V první části jsme sledovali vliv odstranění norka amerického na hnízdní úspěšnost umělých kachních hnízd. Druhá část je souhrnem výsledků testování vlivu predace v závislosti na hnízdní hustotě a typu prostředí.
Does removal of mammalian predators significantly affect success of simulated nests in linear habitats? Case study on American mink Mustela vison \& Predation on simulated duck nests in relation to nest density and habitat type
Keywords: American mink; nest predation; simulated nests; predator removal; Czech Republic; density-dependent predation; nest predators; nest success; American mink; nest predation; simulated nests; predator removal; Czech Republic; density-dependent predation; nest predators; nest success